التحقيق البرلماني كآلية رقابية على أعمال الحكومة - ميسة, بسمة (جامعة الوادي -University eloued, 2022)
على الرغم من الدور الرقابي الذي يمتلكه البرلمان في كونه يتسم بالضعف والمحدودية وعدم الفعالية وذلك بسبب طبيعة تشكيل هاته اللجان في الجزائر الا ان معظم النصوص الدستورية الجزائرية أقرت على ضرورة حق انشاء هاته اللجان في كل قضية تهتم بالمصلحة العامة في حدود نطاق اختصاصها وهذا ما جاء في مضمون التعديل الدستوري 2016الذي اقر أن انشاء لجان التحقيق البرلمانية جاء ليهتم بتحقيق المصلحة العامة للشعب والدولة وهذا ما قد يكون شبه مستحيل بسبب عدم القدرة على احتواء الكم الهائل من متطلبات الشعب.Despite the oversight role that Parliament has in that it is weak, limited and ineffective due to the nature of the formation of these committees in Algeria, most of the Algerian constitutional texts have recognized the necessity of the right to establish these committees in every issue concerned with the public interest within the limits of their competence, and this is what was stated in The content of the 2016 constitutional amendment, which established that the establishment of parliamentary investigation committees came to be concerned with achieving the general interest of the people and the state, and this may be almost impossible due to the inability to contain the huge amount of people’s requirements.
ماستر اداري
Keywords: البرلمان، التحقيق البرلمان، لجان التحقيق; Parliament, inquiry Parliament, commissions of inquiry.